Pengaruh Pemanfaatan Buku KIA dalam Pengkajian ROT dan MAP terhadap Deteksi Dini Pre Eklamsia di Polindes - Kolifah; Erika Agung Mulyaningsih (PROFESSIONAL HEALTH JOURNAL, 2020)
One way to detect the presence of eclampsia is to do early detection using ROT and MAP. Efforts to prevent the occurrence of preeclampsia are with routine antenatal surveillance where one of them is to test the possibility of preeclampsia with conventional examinations namely blood pressure along with urine protein and ROT and MAP examination. The design of this study used a cross sectional design, where observations of independent variables and dependent variables were carried out at the same time. The population in this study was TM III pregnant women who had a book of KIA and conducted ANC examinations in September and October at the Puskesmas. Jelak Ombo Jombang is 87 respondents. Statistical test results show that there is a significant influence between the results of ROT examination with the incidence of pre-eclampsia, there is a significant effect between the results of the MAP examination with the pre-eclampsia event. Examination of ROT and MAP is documented in the KIA book. The KIA book is very effective in utilizing pre-eclampsia early detection through ROT and MAP measurements. The KIA book is a very important for pregnant women, because in the KIA book the condition of the mother is recorded during pregnancy so that information about the state of pregnancy of pregnant women is obtained. The KIA book provides an overview of the condition of the mother at each visit, can also be done early detection of eclampsia and pre-eclampsia through blood pressure and weight of pregnant women.